Karakteristik Fisikokimia dan Organoleptik Isolat Protein Whey Keju dan Tahu Sebagai Suplemen Pangan - Khirzin, Muhammad Habbib; Hilmi, Mustofa; Triasih, Dyah; Rofiqi, Airul Alrizal (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
Whey is a byproduct in the form of water remaining after separating curd and coagulating proteins with acids or enzymes. Whey comes from the leftover processing of cheese and tofu. Whey in Indonesia is generally not used properly, so it only becomes a by-product that can damage the environment. Several alternatives for processing whey liquid waste include whey protein isolate. Exploring the combination of cheese, whey, and tofu as a food supplement is an interesting thing to study. Therefore, this research aims to determine the physicochemical and organoleptic characteristics of cheese and tofu whey protein isolates as a food supplement. The treatments in this study were K1 (100% cheese whey), K2 (50% cheese and 50% tofu whey), and K3 (100% tofu whey). The results showed that the different treatments had a significant effect (P<0.05) on yield parameters, water content, ash content, fat content, protein content, and texture but had no significant effect (P>0.05) on organoleptic properties in the form of color attributes, taste, and aroma. The best treatment was K1 (100% cheese whey protein isolate) based on its physicochemical and organoleptic characteristics. This isolate can be used as a food supplement and as a health therapy.